Effect of hip fracture on prognosis of acute cerebral infarction - Yuan, Jiawen; Zhu, Gang; Zhao, Yuwu; Huang, Jiankang (Clinics, 2021)
OBJECTIVES: Hip fractures are a worldwide public health problem. The incidence of hip fracture is high among the elderly, and it is an important cause of death and disability in this population. This observational study aimed to investigate the effect of acute hip fracture on the recovery of neurological function and the prognosis of patients with acute cerebral infarction, as well as whether surgical treatment of combined acute fracture can improve the prognosis of patients. METHODS: Thirty patients with acute cerebral infarction combined with acute hip fracture, who were hospitalized in two hospitals between January 1, 2013 and December 31, 2019, were included. The patients did not undergo surgical treatment. The control group included patients with common acute cerebral infarction without hip fracture admitted in the same period. The neurological function recovery, hospitalization period, half a year recovery rate, incidence of complications, and one-year mortality rate between the two groups were compared. Eleven patients with acute cerebral infarction combined with hip fracture, who underwent surgical treatment, were selected and compared with those in the non-surgery group. RESULTS: Compared with patients with common acute cerebral infarction, the National Institutes of Health Stroke Scale score of those with acute cerebral infarction combined with hip fracture was higher (7.2±5.4 vs. 5.6%±4.3, p=0.034), the hospitalization period was prolonged (16.1±8.9% vs. 12.2±5.3, p=0.041), and the half a year recovery rate was lower (26.7% vs. 53.3%, p=0.016). Additionally, the incidence of pulmonary infection and lower extremity deep vein thrombosis was increased (30% vs. 11.7%, p=0.03; 6.7% vs. 0, p=0.043). The one-year mortality rate of patients with hip fracture was higher than that of patients with common cerebral infarction (23.3% vs. 6.7%, p=0.027). Compared with the non-surgical group, the good recovery rate after half a year of surgical treatment of the group with cerebral infarction and acute hip fracture had an increasing trend, while the hospitalization cycle, incidence of complications, and one-year mortality rate were all decreased, although this was not statistically significant. CONCLUSIONS: Acute cerebral infarction combined with hip fracture leads to worse neurological recovery, prolonged hospitalization period, increased complications, decreased patient prognosis, and increased one-year mortality. Surgical treatment improves the prognosis of patients with acute cerebral infarction. These findings may provide insights into the management of acute cerebral infarction.